2019
DOI: 10.3390/ma12071063
|View full text |Cite
|
Sign up to set email alerts
|

Light-Emitting Porphyrin Derivative Obtained from a Subproduct of the Cashew Nut Shell Liquid: A Promising Material for OLED Applications

Abstract: In this work, the meso-tetra[4-(2-(3-n-pentadecylphenoxy)ethoxy]phenylporphyrin (H2P), obtained from the cashew nut shell liquid (CNSL), and its zinc (ZnP) and copper (CuP) metallic complexes, were applied as emitting layers in organic light emitting diodes (OLEDs). These compounds were characterized via optical and electrochemical analysis and the electroluminescent properties of the device have been studied. We performed a cyclic voltammetry analysis to determine the Highest Occupied Molecular Orbital (HOMO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Our observations from the emission studies suggest that Por4NT has a strong propensity for aggregation both in solution and in the solid-state. [40] This behavior is in agreement with the conformational DFT results depicted in Figure 2a, which revealed that Por4NT prefers to adopt a highly flat conformation in both the ground state and the excited state. Accordingly, we suggest that the aggregation of Por4NT takes the form of flat-on packing.…”
Section: Resultssupporting
confidence: 90%
“…Our observations from the emission studies suggest that Por4NT has a strong propensity for aggregation both in solution and in the solid-state. [40] This behavior is in agreement with the conformational DFT results depicted in Figure 2a, which revealed that Por4NT prefers to adopt a highly flat conformation in both the ground state and the excited state. Accordingly, we suggest that the aggregation of Por4NT takes the form of flat-on packing.…”
Section: Resultssupporting
confidence: 90%
“…As far as the spectrum of the F8BT emitter is concerned, the bands at 2930 cm −1 and 2850 cm −1 correspond to the stretching mode of the C–H bond, while the band at 1460 cm −1 is due to the C=C stretching mode of an aromatic group [ 31 , 32 ]. Furthermore, the stretching mode between the phenyl rings is detected at 1250 cm −1 , the deformation of aliphatic chain bonds at 1100 cm −1 and the C–H rocking mode at 812 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7] Their applications in displays are due to several unique advantages such as low cost, high contrast, good colour range, exibility, wide viewing angle, fast response time, low driving voltage, low weight, lowtemperature maintenance, and absence of toxic metals. 6,[8][9][10] In their mode of operation, OLED devices transform electrical energy into light. OLED materials encompass a sequential multilayer arrangement of thin organic lms (an emissive layer (EL), a hole-transport layer (HTL) and an electron transport layer (ETL)), all in the middle of two electrodes, assembled via a variety of high technologies.…”
Section: Introductionmentioning
confidence: 99%